Political Ethics in the Perspective of Government Decision-Making and Policy on the Development of the Nation and State - Suhardiman, Taufik (International Journal Labs, 2024)
This research aims to examine political ethics towards government policies, political culture towards government policies, political ethics towards public trust, political culture towards public trust, and government policies towards public trust. The data analysis method employed is quantitative, specifically utilizing correlational research. Correlational research is a general approach focused on estimating covariation among naturally occurring variables. The objective of correlational research is to identify predictive relationships using correlation techniques or statistical methods. The research findings indicate that political ethics significantly influence government policies. Based on the results, it is evident that the public holds a highly positive view of the political ethics of their politicians, indicating a strong belief that politicians operate with high ethical standards in carrying out their public duties. The findings also demonstrate that political culture significantly impacts government policies. This implies that changes or improvements in political culture can directly and significantly influence the direction of policies adopted by local governments. Political ethics have a significant impact on public trust. The data shows that adherence to norms and the adoption of ethical guidelines are crucial factors in building public trust in politicians. Political culture also has a significant influence on effective public trust, consistent with regional development plans, providing measurable outcomes, and undergoing continuous evaluation, which are critical factors in enhancing public trust. Government policies have a significant positive impact on public trust, reflecting the government's commitment to ensuring that implemented policies are not only beneficial but also transparent and accountable.